Harmonization of Labor and Artificial Intelligence - Rio Christiawan (IJRDO - Journal of Business Management, 2019)
President Joko Widodo has established the Making Indonesia 4.0 program as a road map for the nation’s economic development, in the Making Indonesia 4.0 program, one of the main points related to employment is to improve the quality of human resources so that the available workforce becomes more productive and competitively. The challenges and potential of the industry in industrial revolution era 4.0 all parties must realize are artificial intelligence. The 4.0based industrial development road map relies heavily on artificial intelligence connected to the network (online).